2019
DOI: 10.3126/jonmc.v8i1.24446
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profiles and Endoscopic Findings of Patients Undergoing Colonoscopy in Nobel Medical College

Abstract: Background: Colonoscopy is an invasive procedure used both diagnostically and therapeutically. Direct visualization and real-time image of entire large colon and distal terminal ileum makes it superior. Patients are unable to undergo colonoscopy because of the limitation in the developing country. Moreover, limited studies are available in our country regarding the colonic diseases. Materials and Methods: It was a descriptive cross-sectional study done in Nobel Medical College Teaching Hospital, Biratnag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 9 publications
4
3
0
Order By: Relevance
“…The commonest indications for performing elective colonoscopy were chronic diarrhea , altered bowel habits , chronic abdominal pain and bleeding per rectum in the present study. Similar were the findings in the Nepalese study by Shrestha et al 11 Chronic diarrhea and chronic abdominal pain were two common indications for undergoing colonoscopy in the study by Shrestha et al 11 Unlike the study in America, where screening colonoscopy was the commonest indication , this was the least common indication in our present study. In comparative study done in China and USA by Wang et al 17 common finding were polyps both in China and USA followed by colitis.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…The commonest indications for performing elective colonoscopy were chronic diarrhea , altered bowel habits , chronic abdominal pain and bleeding per rectum in the present study. Similar were the findings in the Nepalese study by Shrestha et al 11 Chronic diarrhea and chronic abdominal pain were two common indications for undergoing colonoscopy in the study by Shrestha et al 11 Unlike the study in America, where screening colonoscopy was the commonest indication , this was the least common indication in our present study. In comparative study done in China and USA by Wang et al 17 common finding were polyps both in China and USA followed by colitis.…”
Section: Resultssupporting
confidence: 91%
“…Studies by Salamat et al, 8 in Rawalpindi, Pakistan, Dinesh et al, 9 in Mysore, India, Ngim et al, 10 in Nigeria have demonstrated male predominance amongst colonoscopy patients. Similar male predominance have also been observed in studies by Shrestha et al, 11 and Chaudhary et al, 12 in Nepal. Less opting for colonoscopy in females could be due to social factors , lack of education ,feel of discomfort and embarrassment in telling to family members and physicians regarding ano-rectal pathology and carrying out the procedure itself.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations